Effect of Exercise Duration Toward Heart Rate Recovery in Elderly - Arie Ramdhiani Mahassa; Mohammad Rizki Akbar; Sri Yusnita Irda Sari (Jurnal Kardiologi Indonesia, 2020)
Background: Age-related change in autonomic nerves covers parasympathetic function decrease that hampers heart rate (HR) control. The effective attempt to improve autonomic nervous function for elderly is routine exercise, however exercise duration among elderly is not always standardized. This study is aimed to compare the effect of different exercise duration to post-exercise Heart Rate Recovery (HRR) between two elderly groups with the same frequency, intensity, type criteria of routine exercise. Method: Method was cross-sectional study which compared exercise duration of standardized group (3x90 minutes/week) and unstandardized group (3x30 minutes/week). Group 1 was elders with standardized duration from Healthy Heart Club and Group 2 was elders who take unstandardized duration from Elderly Home in Bandung city. Each group consisted of 43 elders and data were collected in July-August 2019. After one hour of medium intensity exercise, all respondents were examined for resting HR (HRrest), maximum HR (HRmax), one minute post-exercise HR, and four minutes post-exercise HR. HRR was obtained by subtracting HRmax by one minute post-exercise HR and normal if > 12 bpm. Analysis data was done by SPSS with Mann-Whitney U Test, Fisher Chi Square and Logistic regression. Result: Most of respondents were 60-69 years old and female. Respondents in unstandardized group were more low education, hypertension and smoking. The HRrest of both groups was categorized as normal but increased greater (30x/min) in standardized group. The result showed a significant difference in comparation of median HRR (p=0.001) and number of normal and abnormal HRR (p=0.001) between both groups. Gender, smoking and standardized duration of exercise associated with abnormality of HRR, elders who take unstandardized duration have 12.7 times risk to get abnormal HRR. Conclusion: Routine exercise for elderly is recommended in standardized duration with minimal 150 minutes per week in order to increase post-exercise HRR.